(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Peace and happiness are contained in a mind that is constantly positive and pragmatic in attitude towards their goal. A positive human mind can learn, grow, find peace of mind, and can improve his psychological attitude if he/she indulges the self with anything that may be creative in nature, normative in category, or anything else that is existent in this physical world or beyond that, but for a negative mind it is very difficult to find peace of mind. They always find excuses to find a positive destination. They may learn or grow, but either in a negative way or in a way far from finding peace in life. A negative mind is born from ignorance. Therefore, there is a need for enhancing wisdom of life, knowledge of self, nature of the universe, mind power, etc., which leads us towards psychological improvements. A psychologically strong human being can not only achieve his goal but also can lead a path of entrepreneurship. This article tries to put its emphasis on how to get rid of worries by knowing the self and avoid misery created by the material attachment, which is the root cause of psychological degradation and social chaos. Knowing the self in a practical Vedantin way of meditation does not fully ignore the value of the existing world, but at the same time it is emphasising and focusing on the power of the human mind, which is somehow imprisoned with undue attachment of unnecessary worldly objects and emotions. It will focus on the concentration power of the mind and human psychological effects after the proper practice of meditation.